Kerja Sama Nelayan Budidaya Ikan Air Tawar di Danau Ranau: Analisis Ekonomi Syariah terhadap Pola Bagi Hasil (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to analyze the cooperation model of freshwater fish farming fishermen in Lake Ranau and to examine the compatibility of the profit-sharing system with Islamic economic principles. This research employs a qualitative approach using a field study method. Data were collected through in-depth interviews, observations, and documentation involving fish farmers, capital owners, and related stakeholders. The findings indicate that cooperation in freshwater fish farming at Lake Ranau is predominantly informal and based on mutual trust and verbal agreements. Profit-sharing arrangements are determined at the beginning of cooperation; however, they are not fully supported by clear contractual agreements and proportional risk-sharing mechanisms. Substantively, these practices reflect several Islamic economic principles, including mutual assistance (ta’awun), trust (amanah), and distributive justice. Nevertheless, the study identifies an imbalance in risk allocation, where operational risks tend to be borne more heavily by the fish farmers. This study concludes that although the cooperation practices align with the fundamental values of Islamic economics, strengthening a more structured and transparent Islamic-based cooperation model is essential to ensure fairness, balanced risk distribution, business sustainability, and improved welfare of fishermen.